2001
DOI: 10.1093/emboj/20.14.3716
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative regulation of Raf kinase activity and function by phosphorylation

Abstract: Activating and inhibitory phosphorylation mechanisms play an essential role in regulating Raf kinase activity. Here we demonstrate that phosphorylation of C-Raf in the kinase activation loop (residues T491 and S494) is necessary, but not suf®cient, for activation. C-Raf has additional activating phosphorylation sites at S338 and Y341. Mutating all four of these residues to acidic residues, S338D/Y341D/ T491E/S494D (DDED), in C-Raf results in constitutive activity. However, acidic residue substitutions at the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
211
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(224 citation statements)
references
References 42 publications
8
211
0
1
Order By: Relevance
“…Exchange of serine for aspartic acid (D) was intended to mimick the phosphorylation state of serine and has been used in similar studies [13]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Exchange of serine for aspartic acid (D) was intended to mimick the phosphorylation state of serine and has been used in similar studies [13]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As N-region and activation segment phosphorylation act synergistically in Raf-1 activation (Chong et al, 2001), it has been suggested that the constitutively charged N-region predisposes B-Raf for oncogenic hits (Davies et al, 2002;Morrison, 2004;Wellbrock et al, 2004a). Indeed, gain-of-function mutations in the human BRAF gene have been identified in about 70% of malignant melanomas, 30% of papillary thyroid and serous ovarian carcinomas, 15% of colorectal cancers and to a lower frequency in a wide range of other tumours (Davies et al, 2002;Garnett and Marais, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Upon binding to Ras-GTP, 14-3-3 is displaced from phospho-S259 and its re-binding is prevented by S259 dephosphorylation (Dhillon et al, 2002). This induces an open conformation leading to the exposure of the MEK docking site and the phosphorylation of the N-region and activation segment (Chong et al, 2001;Terai and Matsuda, 2005). The N-region plays a critical role in Raf activation (Mason et al, 1999).…”
mentioning
confidence: 99%
“…These events involve changes in Raf-1 localization, phosphorylation and protein-protein interactions (Weinstein-Oppenheimer et al, 2000;Avruch et al, 2001;Wellbrock et al, 2004a). Studies focusing on Raf-1 phosphorylation document both positive and negative effects of Raf-1 phosphorylation (Avruch et al, 2001;Chong et al, 2001). For example, p21 activated kinase (PAK) and Src mediate Raf-1 phosphorylation on positive reg- ulatory sites and augment Raf-1 activity, whereas cAMPdependent protein kinase (PKA) and AKT mediate Raf-1 phosphorylation on negative regulatory sites and inhibit Raf-1 activity.…”
Section: Introductionmentioning
confidence: 99%